Maximization - A. Garmroodi Asil; A. Shahsavand; Sh. Mirzaei (Egyptian Journal of Petroleum)
Over 60% of Iranian natural gases are contaminated with hydrogen sulfide or other sulfur compounds. Khangiran refinery which receives around 50 MMSCMD sour gas with 3.35 mol% H2S as its GTU feed, produces around 45% of Iranian sulfur production. Three of the four existing sulfur recovery units (SRU’s) are initially installed more than 3 decades ago. Such relatively old Claus units with no tail gas clean up facility have usually sulfur recovery efficiencies as low as 90%, due to the low H2S content of the acid gas stream entering SRU process. Eliminating impurities and contaminants such as carbon dioxide form SRU feed stream via proper acid gas enrichment (AGE) process can effectively elevate the Claus combustion chamber temperature and consequently increase the overall sulfur recovery efficiency of the entire SRU process, to achieve more cleaner (SO2 free) air and higher purity product (with brighter color). Three different enrichment schemes are compared together and the most effective and optimal scheme was selected based on their overall sulfur recovery efficiencies. Coupled use of Aspen HYSYS and Promax software was employed to simulate the entire GTU + enrichment section and SRU processes. It is shown that the third scheme can successfully enrich H2S in the acid gas stream from its original value of 0.335 (mole fraction) to more than 0.70. The optimal values of recycled acid gas split ratio, recycled lean amine split ratio and enrichment tower pressure for this scheme are found to be around 0.8, 0.14 and 60 psia, respectively. To further reduce the sulfur dioxide emission of the entire refining process, two scenarios of acid gas or air preheats are investigated when either of them is used simultaneously with the third enrichment scheme. The maximum overall sulfur recovery efficiency and highest combustion chamber temperature is slightly higher for acid gas preheats but air preheat is more favorable because it is more benign. To the best of our knowledge, optimization of the entire GTU + enrichment section and SRU processes has not been addressed previously.